2022
DOI: 10.1038/s41598-022-05943-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and isotherm insights of Diclofenac removal by sludge derived hydrochar

Abstract: Recently, hydrothermal carbonization emerges as the most viable option for the management of solid waste with high moisture content. Sludge derived hydrochar is used as an adsorbent for emerging contaminants or micro-pollutants in the domain of sustainability. Current study demonstrates the KOH activation of hydrochar produced from paper board mill sludge and evaluates its removal potential of a Non-steroidal anti-inflammatory drug, Diclofenac from aqueous solution. The activated hydrochars exhibited porous, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
(60 reference statements)
2
5
0
Order By: Relevance
“…In this case, the native biomass of M. aeruginosa ACCMU‐118 exhibited a DCF binding site capacity of 12.67 μmol. However, the Temkin model performed poorly in fitting the experimental data, consistent with other studies 79 …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this case, the native biomass of M. aeruginosa ACCMU‐118 exhibited a DCF binding site capacity of 12.67 μmol. However, the Temkin model performed poorly in fitting the experimental data, consistent with other studies 79 …”
Section: Resultssupporting
confidence: 89%
“…However, the Temkin model performed poorly in fitting the experimental data, consistent with other studies. 79 Sorption and removal of DCF by pretreated biomass Previous studies have indicated limited accessibility of binding sites in algal biosorbents for metal ions. 45,[80][81][82] Chemical treatments have been proposed to enhance binding site accessibility.…”
Section: Equilibrium Sorptionmentioning
confidence: 99%
“…The PZC point determined by this method is 7.3, by which it can be concluded that neither positive nor negative charges dominate the surface. This result is similar to the result of 7.6 obtained by Oumabady et al for hydrochar obtained from paper board mill sludge [44].…”
Section: Characterisation Of Obtained Hydrocharsupporting
confidence: 92%
“…Langmuir isotherm model assumes monolayer coverage of the homogenous energy distributed active sites containing surface (Islam et al, 2018). Instead of predicting monolayer coverage, the Freundlich isotherm model utilizes the concept of multilayer sorption (Oumabady et al, 2022) of foreign molecules, e.g., dyes, metals, etc., on the heterogeneous surfaces of the sorbents (Takkar et al, 2022). This study analyzed the MO molecules and biochar system using Langmuir and Freundlich models.…”
Section: Resultsmentioning
confidence: 99%